2015
DOI: 10.1111/anu.12324
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of digestibility in agastric fish based on stripping method - apparent nutrient, energy and amino acid digestibilities of common feed ingredients for carp diets (Cyprinus carpio)

Abstract: Apparent nutrient, energy and amino acid (AA) digestibilities of wheat starch (WS), corn starch (CS), pea protein concentrate (PPC), soy protein concentrate (SPC), corn gluten meal (CGM) and soybean meal (SM) were assessed indirectly in common carp by applying the marker‐based indicator method. Each test diet consisted of 70% reference diet and 30% test ingredient. Stripping as faeces collection technique was applied to obtain faecal material two times a day for 9 weeks. Apparent digestibilities of ingredients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…Diets and DEF/DEC were formulated on digestible basis in this study. Apparent nutrient, energy and AA digestibilities of all ingredients being inserted in this trial were determined in a previous trial (Heinitz et al., ). Also in a study from Lee, Jeon, and Lee (), determining effects of lipids and protein in diets for juvenile rockfish ( Sebastes schlegeli ), nutrient and energy contents were declared and diets were formulated on digestible basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets and DEF/DEC were formulated on digestible basis in this study. Apparent nutrient, energy and AA digestibilities of all ingredients being inserted in this trial were determined in a previous trial (Heinitz et al., ). Also in a study from Lee, Jeon, and Lee (), determining effects of lipids and protein in diets for juvenile rockfish ( Sebastes schlegeli ), nutrient and energy contents were declared and diets were formulated on digestible basis.…”
Section: Discussionmentioning
confidence: 99%
“…The central diet contained 230 g/kg DP and had a DEF/DEC of 1 (run 5–12 in Table ). For calculations of diets on digestible basis, apparent digestibility data were taken from prior trial (Heinitz, Lemme, & Schulz, ) and missing values were taken from literature (Hertrampf & Piedad‐Pascual, ; Espe, Lemme, Petri, & El‐Mowafi, ; Espe, Hevrøy, Liaset, Lemme, & El‐Mowafi, ; NRC ). The experimental diets were produced in form of 4‐mm‐diameter sinking extrudates at “Research Diet Services” (RDS, the Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Evaluating and monitoring the nutritional potential of the food, not only can be useful for nutritional quality control strategists at the industrial levels (Fontaine et al, 2001;Lemos et al, 2009) but also restricts contamination through sh production (Hardy, 2010;Karapanagiotidis et al, 2019;Lee, 2002). Meanwhile, different methods of feces collection such as dissection, aspiration in anal, sedimentation and ltration, fecal collection with pipetting, decantation, and stripping have a signi cant impact on calculated and estimated of nutrient digestibility (Glencross et al, 2007) and lead to overestimation or underestimate of digestibility (Heinitz, Lemme, & Schulz, 2016). Austreng et al (1978) observed that the technique of collecting feces by pressing on the abdomen of sh lead to underestimating digestibility of protein and energy or sedimentation collection technique can lead to overestimation of digestibility of food components due to the leaching of nutrients into the water (Glencross et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of the literature on feed efficiency discusses traditionally the simplest indicators, that is feed conversion ratio (FCR) or its inverse, feed efficiency ratio (FER) calculated as the simple ratio of input and output or vice versa, where the feed is the input and the output is the weight gain. Better digestibility of nutrients means lower FCR so a determination of apparent digestibility coefficient (ADC) makes part of nowadays' feeding studies (Grisdale-Helland et al, 2013;Heinitz et al, 2015). Although the determination of ADC doesn't have a generally used, standardized method till now, it has many advantages over measuring correctly the metabolizable energy of nutrients of fish foods or industrial feeds (Lovell, 1989).…”
Section: Introductionmentioning
confidence: 99%